Pandemic pedagogies teaching and learning during the COVID-19 pandemic - Ryan, J. Michael (Routledge, Taylor & Francis Group, 2023)
"Pandemic Pedagogies: Teaching and Learning during the COVID-19 Pandemic provides critical insights into the impact of the pandemic on the education system, pedagogical approaches and educational inequalities. Education is often touted as the best way to promote social mobility and producing informed members of society. The pandemic has significantly threatened those goals by temporarily disrupting education and exacerbating disparities in the education system. The scholarship in this volume takes a closer look at many of the issues at the heart of the educational process including teacher self-efficacy, the gendered and racialized impacts of the pandemic on education, school closures, and institutional responses. Drawing on the expertise of scholars from around the world, the work presented here represents remarkable diversity and quality of impassioned scholarship on the impact of COVID-19 and is a timely and critical advance in knowledge related to the pandemic"
Keywords: Pandemie; COVID-19; Unterricht; Pädagogik; Lehrtätigkeit; Education / History / 21st century; COVID-19 Pandemic, 2020- / Social aspects; Education; Social aspects; Since 2000; History